2013
DOI: 10.3109/08880018.2013.825683
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of HFE Polymorphisms on Cardiac Iron Overload in Patients with Beta-Thalassemia Major

Abstract: The HFE polymorphisms had no effect on cardiac iron overload. However, pulmonary vein atrial reversal flow velocity measurements can provide important information for detecting diastolic dysfunction during cardiac follow-up of patients with HFE polymorphisms. Studies with more patients are needed to provide more information regarding this matter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Aysen Turedi et al in their study among 33 patients with beta thalassaemia major found only H63D pathogenic variant among 6 patients ( 5heterozygotes and 1 homozygote) 19 . Similarly, in our study 15.4% had H63D pathogenic variant and the C282Y and S65C pathogenic variants were not seen.…”
Section: Discussionmentioning
confidence: 90%
“…Aysen Turedi et al in their study among 33 patients with beta thalassaemia major found only H63D pathogenic variant among 6 patients ( 5heterozygotes and 1 homozygote) 19 . Similarly, in our study 15.4% had H63D pathogenic variant and the C282Y and S65C pathogenic variants were not seen.…”
Section: Discussionmentioning
confidence: 90%
“…Aysen Turedi et al in their study among 33 patients with beta thalassaemia major found only H63D pathogenic variant among 6 patients (5 heterozygotes and 1 homozygote) [ 27 ]. Similarly, in our study 15.4% had H63D pathogenic variant and the C282Y and S65C pathogenic variants were not seen.…”
Section: Discussionmentioning
confidence: 99%
“…When cell has adequate amounts of iron, it competitively binds to TFR and prevents iron absorption via endocytosis 6 . To date, many polymorphisms of the HFE have been identified out of which H63D and C282Y have been reported to be comparatively more frequent 7 . H63D polymorphism entails replacement of aspartic acid 63 by histidine due to nonsynonymous substitution of cytosine with guanine at nucleotide 187 of the HFE gene 8 .…”
Section: Introductionmentioning
confidence: 99%